2003
DOI: 10.1093/jnci/djg118
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Retroviral Tax Oncoproteins With Tristetraprolin and Regulation of Tumor Necrosis Factor-  Expression

Abstract: Tax, through its interactions with the TTP repressor, indirectly increases TNF-alpha expression. This observation is of importance for the cell transformation process induced by leukemogenic retroviruses, because TNF-alpha overexpression plays a central role in pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 84 publications
2
51
0
Order By: Relevance
“…As demonstrated previously, MSX2 protein fused to GFP localizes mainly in the cell nucleus (29). To confirm and extend these observations, the MSX2 protein was tagged with the c-Myc epitope (in plasmid pcDNAMSX2-c-Myc).…”
Section: Tax and Msx2 Interact In Vitro And Coimmunoprecipitate In Cellsupporting
confidence: 66%
See 1 more Smart Citation
“…As demonstrated previously, MSX2 protein fused to GFP localizes mainly in the cell nucleus (29). To confirm and extend these observations, the MSX2 protein was tagged with the c-Myc epitope (in plasmid pcDNAMSX2-c-Myc).…”
Section: Tax and Msx2 Interact In Vitro And Coimmunoprecipitate In Cellsupporting
confidence: 66%
“…Plasmids pADMSX2 and pSV40 code for the Gal4-activating domain (AD) fused to the human MSX2 protein or the amino acids 84 -708 of the SV40 large T-antigen, respectively. Vector pGexTax codes for a fusion protein between Tax and the glutathione S-transferase (GST) (29).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylation of TTP may also affect its association with exosome [65], stress granule [36], nucleoporin CAN/Nup214 [66], and retroviral Tax oncoproteins [67]. Phosphorylation may play a role in TTP-mediated delivery of ARE-mRNAs to processing bodies for translational silencing and mRNA decay since ARE-mRNA localization in processing bodies is mediated by the phosphorylation site-rich N-and C-termini of TTP [68].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…The amino acid sequences used in the alignment include human (NP_003398) [77], mouse (NP_035886) [27], rat (P47973) [78], bovine (P53781) [79], sheep (AY462109) [67], pig (AJ943797, CB288050, CB286240, DY416794 and DY419026) [80], horse (CD536573 and CD536523), chimpanzee (CR555169 andXM_001136016) and dog (AAEX01054372.1 and AAEX01054371.1) [81]. The sequences were aligned with the PILEUP program from GCG.…”
Section: Key Issuesmentioning
confidence: 99%
“…The exact mechanism whereby Tax is recruited to SGs remains to be elucidated. We have previously reported that Tax interacts with TTP, an ARE-binding protein involved in the turnover of specific cellular transcripts (Twizere et al, 2003). The region of Tax that mediates the interaction with TTP lies in the C-terminal portion of the protein and is thus still present in the D2-22 Tax mutant.…”
Section: Discussionmentioning
confidence: 99%